Soft chemistry synthesis method of ZnAl2−xCrxO4 spinel: Structural, morphological, optical and photocatalytic properties. (December 2022) - Gingasu, Dana; Culita, Daniela C.; Calderon Moreno, Jose Maria; Oprea, Ovidiu; Marinescu, Gabriela; Preda, Silviu; Kuncser, Andrei
Abstract: The precursor method was employed to prepare ZnAl2−x Crx O4 (x = 0, 0.25, 0.5, 0.75, 1) using tartaric acid as a ligand. Five tartarate compounds were isolated as precursors for the obtaining of zinc aluminate and chromium-substituted zinc aluminate. These coordination compounds were characterized by elemental chemical analysis, infrared (IR) and ultraviolet visible (UV-Vis) spectroscopy, and thermal analysis. The influence of Cr 3+ substitution on the structure, morphology and optical properties of the synthesized mixed oxides was investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), infrared, Raman and UV-Vis spectroscopy, and nitrogen adsorption – desorption analysis. The XRD patterns and Raman spectra confirmed the formation of spinel structure. The mean crystallite size varied from 18 to 22 nm SEM and EDS showed uniform composition and microstructure of the ZnAl2−x Crx O4 nanocrystalline powders. The values of the optical energy bandgap for the samples were found to be in the 3.92 – 2.85 eV range. The photocatalytic performance in the degradation reaction of Eosin Y (EY) under visible light irradiation was evaluated. The Eosin Y degradation efficiency values were obtained between 48% and 80% after 75 min. The best photocatalytic result was obtained for the sample with the highest amount of chromium. Graphical Abstract: ga1